Engineered Vasculogenic Extracellular Vesicles Drive Nonviral Direct Conversions of Human Dermal Fibroblasts into Induced Endothelial Cells and Improve Wound Closure. Issue 3 (22nd December 2022) - Rincon‐Benavides, Maria A.; Mendonca, Natalia Claire; Cuellar‐Gaviria, Tatiana Z.; Salazar‐Puerta, Ana I.; Ortega‐Pineda, Lilibeth; Blackstone, Britani N.; Deng, Binbin; McComb, David W; Gallego‐Perez, Daniel; Powell, Heather M.; Higuita‐Castro, Natalia
Abstract: Vasculogenic cell therapies have emerged as a powerful tool to increase vascularization and promote tissue repair/regeneration. Current approaches to cell therapies, however, rely mostly on progenitor cells, which pose significant risks (e.g., uncontrolled differentiation, tumorigenesis, and genetic/epigenetic abnormalities). Moreover, reprogramming methodologies used to generate induced endothelial cells (iECs) from induced pluripotent stem cells rely heavily on viral vectors, which pose additional translational limitations. This work describes the development of engineered human extracellular vesicles (EVs) capable of driving reprogramming‐based vasculogenic therapies without the need for progenitor cells and/or viral vectors. EVs are derived from primary human dermal fibroblasts (HDFs), and are engineered to pack transcription factor genes/transcripts of ETV2, FLI1, and FOXC2 ( EFF ). In addition to EFF, the engineered EVs are also loaded with transcripts of angiogenic factors (e.g., VEGF‐A, VEGF‐KDR, FGF2). In vitro and in vivo studies indicate that such EVs effectively transfected HDFs and drive direct conversions towards iECs within 714 days. Finally, wound healing studies in mice indicate that engineered EVs lead to improved wound closure and vascularity. Altogether, these results show the potential of engineered human vasculogenic EVs to drive direct reprogramming processes of somatic cells towards iECs, and facilitate tissue repair/regeneration. Abstract : Engineered human EVs loaded with ETV2, FLI1, and FOXC2 (EFF), can effectively drive vasculogenic reprogramming in human dermal fibroblasts and aid with in vivo tissue repair and regeneration. Such EVs have the potential to serve as a powerful nanocarrier platform for vasculogenic factors to treat a myriad of ischemic disorders.